Microbiological Evaluation of Different Types of Branded and Non-branded Ready-to-Eat Snacks Sold in Elementary Schools of District Peshawar, Pakistan - Hussain, Arshad; Rahman, Zia Ur; Khan, Muddasir (BioScientific Review, 2023)
The lack of hygiene in the preparation and packing of ready-to-eat foods is fast becoming a serious public health concern, especially for school children. The intervention of different pathogenic microorganisms in these foods poses the risk of foodborne disease outbreaks. The current study was designed to assess bacterial contamination in different types of ready-to-eat (branded and non-branded) snacks purchased from September 2021 to December 2021 in various elementary schools of Peshawar, Pakistan. A total of 20 samples were collected and analyzed using the pour plate method for total plate count (TPC). Moreover, the multiple fermentation tube method was used for total coliforms (TC) and fecal coliforms (FC). Escherichia coli isolates were identified using E. coli O157:H7 latex test reagent kit Pro Lab, Canada. The results revealed contamination by TPC (6.67%), TC (40%), FC (33.33%), and E. coli (20%) in the samples. These values were higher than the permissible limits set by Food and Agriculture Organization (FAO). Hence, it was concluded that there is a practice gap in food safety knowledge among ready-to-eat food vendors. The vendors are usually untrained and lack the knowledge of proper hygiene and food handling procedures. It is suggested here that the government should pay special attention towards improving public awareness regarding food safety and quality of ready-to-eat foods sold in Peshawar, Pakistan.